ESTABLISHMENT OF VIRTUAL FRACTURE CLINIC IN PRINCESS ROYAL HOSPITAL TELFORD: EXPERIENCE AND RECOMMENDATIONS DURING THE FIRST 9 MONTHS - Khaleeq, Tahir; Lancaster, Patrick; Fakoya, Keji; Black, Martin; Littlehales, Julie; Ferreira, Pedro; Ahmed, Usman (Journal of Ayub Medical College Abbottabad, 2022)
Background: Virtual fracture clinics (VFC) have been shown to be a safe and cost-effective way of managing outpatient referrals to the orthopaedic department. During the coronavirus pandemic there has been a push to reduce unnecessary patient contact whilst maintaining patient safety. Methods: A protocol was developed by the clinical team in collaboration with Advanced Physiotherapy Practitioners (APP) on how to manage common musculoskeletal presentations to A&E prior to COVID as part of routine service development. Patients broadly triaged into 4 categories; discharge with advice, referral to VFC, referral to face to face clinic or discussion with on call team. The first 9 months of data were analysed to assess types of injury seen and outcomes. Results: In total 2489 patients were referred to VFC from internal and external sources. Seven hundred and thirty-four patients were discharged without follow-up and 182 patients were discharged for physiotherapy review. Only 3 patients required admission. Regarding follow-ups, 431 patients had a virtual follow-up while 1036 of patients required further face to face follow up. Eighty-seven patients were triaged into subspecialty clinics. Thirty-seven patients were felt to have been referred inappropriately. Discussion: British Orthopaedic Association guidelines suggest all patients need to be reviewed within 72 hours of their orthopaedic injury. Implementation of a VFC allows this target to be achieved and at the same time reduce patient contact. Almost half the patients were discharged following VFC review, the remaining patients were appropriately followed up. This is especially relevant in the current pandemic where reducing unnecessary trips to hospital will benefit the patient as well as make the most of the resources available.